Effect of particle size of sand and surface properties of reinforcement on sand-geosynthetics and sand–carbon fiber polymer interface shear behavior. (September 2020) - Namjoo, Amir Mostafa; Jafari, Khashayar; Toufigh, Vahid
Abstract: Soil-reinforcement interface friction is an important geotechnical engineering parameter that needs to be assessed in achieving a safe and cost-effective design. In this study, the effect of mean particle size (D50 ), type, and surface properties of reinforcements on shear behavior of soil-reinforcement interface were evaluated using direct shear test. Three types of sands with different D50 and similar properties, and six types of reinforcing materials with different surface features; three conventional types (GTX, GGB, and GC) and three novel types (CFRP, SPSCFRP, and GeoFRP), were used for this purpose. The direct shear test (DST) device was modified and proposed to determine the shear strength and friction angle between soil and reinforcements at different normal stresses. Test results revealed that interface shear strength between soil and reinforcements depends on both particle size of the sand and type of reinforcement. The influence of particle size was more significant when coarser size was used since the interlocking behavior occurred between the sand particles and the asperities of reinforcing material. However, the surface roughness of reinforcement affected the shear strength to an extent.